Pengolahan Air Gambut dengan Magnetik Karbon/Clay Komposit dari Spent Bleaching Earth Limbah Pengolahan Minyak Sawit - Rahmawati, Risma; Nigravita, Annisa Nurfadilla; Larasati, Indira; Mahafani, Rafshel Heikal; Syafutra, Reihan; Sunardi, Sunardi (Nusantara Journal of Science and Technology, 2024)
Spent Bleaching Earth (SBE) is one of the largest wastes produced from the crude palm oil (CPO) refining industry. SBE can be converted into carbon for various purpose. Modification of SBE into magnetic carbon/clay composites can improve its performance. Modification SBE into magnetic carbon/clay composites can improve the pore structure and surface of the material. This research aims to synthesize magnetic carbon/clay composites from SBE using the co-prepitation method and apply it to peat water treatment by degradation method. The results obtained from this research, organic compounds in peat water can be degraded as much as 87.1875% within 20 minutes. In addition, the pH of peat water has increases and the intensity of peat water color has been decrease.